2015
DOI: 10.1002/ardp.201400322
|View full text |Cite
|
Sign up to set email alerts
|

N‐(2‐(Piperazin‐1‐yl)phenyl)arylamide Derivatives as β‐Secretase (BACE1) Inhibitors: Simple Synthesis by Ugi Four‐Component Reaction and Biological Evaluation

Abstract: A novel series of N-(2-(piperazin-1-yl)phenyl)aryl carboxamide derivatives were simply synthesized by Ugi-multicomponent reaction as β-secretase (BACE1) inhibitors. The BACE1 inhibitory activity of the synthesized compounds was examined using a Forester resonance energy transfer (FRET)-based assay. Among the tested compounds, the N-(5-bromo-2-(4-phenylpiperazine-1-yl)phenyl)thiophene-carboxamide derivative 14 containing the N-cyclohexyl indole acetamide moiety showed superior BACE1 inhibition at 10 and 40 µM. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Similar to the well-studied coumarines, which have been found in various species of plants, 2-iminocoumarine derivatives are used as dyes , and fluorescent sensors for detection of metal ions in a very low concentration. Furthermore, these fluorophores have low cytotoxicity and can selectively stain organelles in living cells . A lot of 2-iminocoumarines possess high antibacterial, antifungal, anti-HIV, antimicrobial, , anti-Alzheimer , activity. Recently, it has been found that arylsubsituted iminocoumarines have revealed high antitumor and anticancer activity. …”
Section: Introductionmentioning
confidence: 99%
“…Similar to the well-studied coumarines, which have been found in various species of plants, 2-iminocoumarine derivatives are used as dyes , and fluorescent sensors for detection of metal ions in a very low concentration. Furthermore, these fluorophores have low cytotoxicity and can selectively stain organelles in living cells . A lot of 2-iminocoumarines possess high antibacterial, antifungal, anti-HIV, antimicrobial, , anti-Alzheimer , activity. Recently, it has been found that arylsubsituted iminocoumarines have revealed high antitumor and anticancer activity. …”
Section: Introductionmentioning
confidence: 99%
“…The kit was purchased from Invitrogen (former Pan Vera Corporation) and the evaluation procedure was conducted according to the manufacturer's instructions. [ 24–26 ] BACE1 (purified baculovirus‐expressed enzyme) was diluted using buffer (50 mM sodium acetate, pH 4.5) to prepare a 3× working solution of 1 U/ml. The peptide substrate (RhEVNLDAEFK‐Quencher) was also diluted in the same buffer to obtain the 3× stock solution.…”
Section: Methodsmentioning
confidence: 99%
“…To choose and validate the docking algorithm, the tropolone as cognate ligand inside the 2Y9X was redocked. Finally, the best docking confirmations with minimum binding energy were visualized using Discovery studio (Edraki et al, 2015).…”
Section: Molecular Dockingmentioning
confidence: 99%